Are Blastocystis hominis and Cryptosporidium spp. playing a positive role in colorectal cancer risk? A systematic review and meta-analysis - Ali Taghipour; Esmail Rayatdoost; Amir Bairami; Saeed Bahadory; Amir Abdoli (Infectious Agents and Cancer, 2022)
Abstract Objective Intestinal protozoa Blastocystis hominis and Cryptosporidium spp. are two influential factors in intestinal complications and malignancies. In present study, we estimated the pooled prevalence and odds ratio (OR) of the two parasites in colorectal cancer (CRC) patients and their possible association with the deadly disease. Method Our systematic search was conducted for published researches between January 1, 2000 and April 30, 2022 by using four international databases include Scopus, PubMed, and Web of Science as well as Google scholar search engine. The random- and fixed-effects models were used to estimate the pooled prevalence, OR, and 95% confidence interval (CI) by comprehensive meta-analysis (V2.2, Bio stat) software. Inclusion and exclusion criteria were applied. Results Thirteen papers (seven case–control and six cross-sectional studies) for B. hominis/CRC and six papers (two case–control and four cross-sectional studies) for Cryptosporidium spp./CRC were eligible to include in data synthesis. Pooled prevalence of B. hominis and Cryptosporidium spp. in CRC patients was calculated to be 26.8% (95% CI 19.4–35.7%) and 12.7% (95% CI 6.8–22.5%), respectively. Based on case–control studies, significant difference was found between case and controls in both protozoa (B. hominis OR 2.10; 95% CI 1.39–3.18% vs. Cryptosporidium spp. OR 5.06; 95% CI 1.8–13.6%). Considering the Blastocystis subtypes, ST1 (5/6; 83.33% studies) and ST3 (5/6; 83.33% studies) had the highest number of reports in CRC patients. Regarding the Cryptosporidium species, only C. parvum and C. hominis were reported. Conclusion Given the significant prevalence of both parasites in CRC patients and their statistically significant association, there is a need to pay more attention to these two intestinal parasites in under treatment patients.